Manajemen Cairan Pada Pasien Dengan Diabetes Ketoasidosis (DKA): Literatur Review - Sandra Pebrianti; Bambang Aditya Nugraha; Iwan Shalahuddin; Theresia Eriyani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
DKA is a state of decompensation of metabolic chaos characterized by triassic hyperglycemia, acidosis, and ketosis which is one of the most serious and life-threatening acute complications of metabolic diabetes mellitus. Diabetic Ketoacidosis (DKA) requires proper treatment and immediate treatment. Management of insulin therapy, intravenous administration of fluids is a key component of DKA management to expand intravascular, interstitial, and intracellular volumes. This Literature Review aims to determine the influence of fluid management in patients with diabetes ketoacidosis. The author uses the method used to conduct a literature review is to search through the internet. Search literature through the internet based on several criteria, namely journals published in the last 10 years. The literature search uses the PubMed, Sage Journals, and Science Direct databases. Keywords used ''Fluid Management AND Diabetes Ketoacidosis (DKA)''. Then sorted by inclusion criteria, publication year 2017-2022, experimental research design, and written in Indonesian or uk. Based on the results of the study, it can be concluded that there are six fluid administration interventions in Diabetes Ketoacidosis (DKA) patients, namely crystalloid fluid, saline fluid, lyte-148 plasma, potassium, plasma lyte A and the use of two fluids (electrolyte fluid + dextrose). DKA management includes adequate replacement of fluids and electrolytes, especially potassium, as well as continuous administration of insulin. The top priority in the management of DKA is one of them is fluid therapy.